2018
DOI: 10.1186/s12888-018-1687-x
|View full text |Cite
|
Sign up to set email alerts
|

The validity of proxy-based data on loneliness in suicide research: a case-control psychological autopsy study in rural China

Abstract: BackgroundThere is a lack of evidence for the role of loneliness on suicide using psychological autopsy method, and the validity of proxy informants’ reports on loneliness is not well established. This study aimed to investigate the validity of proxy respondent reports on loneliness, and the reliability and validity of the University of California Los Angeles Loneliness Scale-6 (ULS-6) as used in psychological autopsy method with rural elderly people in China.MethodsTwo hundred forty-two suicide cases and 242 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 37 publications
2
31
0
1
Order By: Relevance
“…Our previous studies had proved the validity of proxy data in in psychological autopsy study (26,27). We also compared the proxy-based information of pain intensity with the data reported by the subjects themselves in the living control group.…”
Section: Data Combinationmentioning
confidence: 99%
“…Our previous studies had proved the validity of proxy data in in psychological autopsy study (26,27). We also compared the proxy-based information of pain intensity with the data reported by the subjects themselves in the living control group.…”
Section: Data Combinationmentioning
confidence: 99%
“…Jednocześnie uzależnienie od alkoholu indukuje objawy podobne do tych obserwowanych w dużym epizodzie depresyjnym, wpływa negatywnie na relacje osoby uzależnionej z bliskimi, a także zmniejsza poziom wsparcia społecznego [8]. Liczne badania potwierdzają, że samotność oraz niski poziom wsparcia społecznego zwiększają ryzyko wystąpienia tendencji samobójczych [11][12][13], zaś pozostawanie w stabilnym związku [14] oraz utrzymywanie silnych więzi rodzinnych [15] istotnie redukuje to ryzyko. Dodatkowo upośledzenie funkcji czołowych będące możliwym skutkiem nadużywania alkoholu, znacząco upośledza zdolność do efektywnego rozwiązywania problemów [8].…”
Section: Wstępunclassified
“…At the same time, addiction to alcohol induces symptoms similar to those observed in a major depressive episode, negatively affects the relationship of the addicted person with the loved ones, and also reduces the level of social support [8]. Numerous studies confirm that loneliness and a low level of social support increase the risk of suicidal tendencies [11][12][13], while staying in a stable relationship [14] and maintaining strong family ties [15] significantly reduce this risk. In addition, the impairment of frontal functions, which is a possible consequence of alcohol abuse, significantly impairs the ability to effectively solve problems [8].…”
Section: Introductionmentioning
confidence: 97%
“…Loneliness is also one of the risk factors for depression, which constitutes a huge impact on the health of the elderly. Yan zhi min and other researchers found that a single sense of loneliness does not affect the mortality rate of the elderly, but when loneliness and depression coexist, the mortality rate will increase significantly (Niu, Jia, Ma et al, 2018). This may be due to the influence of loneliness as a mediator on the immune system and physiological responses, which may lead to a decrease in sleep quality and an increase in the incidence of cardiovascular and cerebrovascular diseases.…”
Section: Introductionmentioning
confidence: 95%